Understanding educational complexity : integrating practices and perspectives for 21st century leadership - Kershner, Brad (Educational leadership and leaders in contexts, 2021)
"Our ability to understand and improve the field of education depends upon our ability to understand human development, culture, and society. We cannot understand what is happening in schools unless we understand the context in which schools exist. Through meaningful stories of school leadership and critical reflections on theories of complex systems, this book offers a framework for understanding how the intractable dilemmas of education reflect and embody the social, cultural, and developmental patterns of society. From the concrete dilemmas of school leadership to the abstract vistas of integral meta-theory, this book is a guide to understanding how it all fits together, and how to encourage the holistic growth of students, teachers, leaders, and educational systems"--